Pentahelix Model to Create Shared Value in Empowering the People of Winong Village, Gempol District, Pasuruan Regency - Aminullah Aminullah; Any Urwatul Wusko (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study addresses the gap in understanding how such policies influence local economies, specifically in Winong Village. The research introduces a novel application of the pentahelix model, focusing on private actors' role in fostering